2019
DOI: 10.1519/jsc.0000000000002059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Volume High-Intensity Interval Exercise and Continuous Exercise on Delayed-Onset Muscle Soreness in Untrained Healthy Males

Abstract: The aim of this study was to compare the effect of a single session of a low-volume high-intensity interval exercise (HIIE) and a continuous exercise (CE) on the magnitude of delayed onset-muscle soreness (DOMS) in untrained healthy males. Fifteen participants (25.1±4.4 years) completed 2 experimental sessions in a randomized order: (a) low-volume HIIE: 10 x 60 s at 90% of maximal velocity (MV) interspersed with 60s of active recovery at 30% of MV; and (b) CE: 20 min at 60% of MV. Pressure-pain threshold (PPT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Next, we explored BMD and MV to evaluate whether an adaptive HR response to the exercise training protocol was beneficial to bone and muscle health. Our findings corroborate previous evidence that an interval exercise program that applies the FITT principle and is developed based on former studies can increase BMD [16][17][18][19][20][21][22][23]39,40]. The 12.6% increase in BMD that we observed is consistent with human studies that found an association between BMD and injury [41] or disease [42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Next, we explored BMD and MV to evaluate whether an adaptive HR response to the exercise training protocol was beneficial to bone and muscle health. Our findings corroborate previous evidence that an interval exercise program that applies the FITT principle and is developed based on former studies can increase BMD [16][17][18][19][20][21][22][23]39,40]. The 12.6% increase in BMD that we observed is consistent with human studies that found an association between BMD and injury [41] or disease [42].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, exercise (e.g., sprinting, jogging, weightlifting, swimming) can be a powerful intervention for the prevention and treatment of these conditions in humans [16][17][18]. In several other studies, participants of different ages and genders showed positive changes in BMD, MV, and bone turnover serum biomarkers (e.g., bone-specific alkaline phosphatase, deoxypyridinoline, and calcium) after exercise designed according to the Frequency, Intensity, Time/duration, Type, Volume, and Progression (FITT-VP) principle [19][20][21][22][23]. To date, however, there has been little scientific examination of the effect of exercise on bone and muscle health in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the low-volume HIIT group performed more work bouts, it is reasonable to think that the participants from this group had a higher internal load, probably mediated by a more pronounced metabolic stress (i.e., blood lactate accumulation and pH disturbance), than participants from the very-low-volume HIIT group. In addition, a recent study showed that low-volume high-intensity interval exercise generates a mild delayed-onset muscle soreness 24 hours after exercise, similar to moderate continuous exercise in untrained healthy males (Farias Junior et al., 2017). This result suggests that the very-low-volume HIIT may have even lower delayed-onset muscle soreness, which is particularly important for inexperienced/untrained individuals in HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exercise (e.g., sprinting, jogging, weightlifting, swimming) can be a powerful intervention for the prevention and treatment of these conditions in humans [12][13][14] . In several other studies, participants of different ages and genders showed positive changes in BMD, MV, and bone turnover serum biomarkers (e.g., bone-speci c alkaline phosphatase, deoxypyridinoline, and calcium) after exercise designed according to the Frequency, Intensity, Time/duration, Type, Volume, and Progression (FITT-VP) Principle [15][16][17][18][19] . To date, however, there has been little scienti c examination of the effect of exercise on bone and muscle health in dogs.…”
Section: Introductionmentioning
confidence: 96%